Differential regulation of mTORC1 and mTORC2 is critical for 8-Br-cAMP-induced decidualization - Baek, Mi-Ock (Exp Mol Med, 2018)
Human endometrium decidualization, a differentiation process involving biochemical and morphological changes, is a prerequisite for embryo implantation and successful pregnancy. Here, we show that the mammalian target of rapamycin (mTOR) is a crucial regulator of 8-bromoadenosine 3’,5’-cyclic monophosphate (8-Br-cAMP)-induced decidualization in human endometrial stromal cells. The level of mSin1 in mTOR complex 2 (mTORC2) and DEPTOR in mTOR complex 1 (mTORC1) decreases during 8-Br-cAMP-induced decidualization, resulting in decreased mTORC2 activity and increased mTORC1 activity. Notably, DEPTOR displacement increases the association between raptor and insulin receptor substrate-1 (IRS-1), facilitating IRS-1 phosphorylation at serine 636/639. Finally, both S473 and T308 phosphorylation of Akt are reduced during decidualization, followed by a decrease in forkhead box O1 (FOXO1) phosphorylation and an increase in the mRNA levels of the decidualization markers prolactin (PRL) and insulin-like growth factor-binding protein-1 (IGFBP-1). Taken together, our findings reveal a critical role for mTOR in decidualization, involving the differential regulation of mTORC1 and mTORC2.